Child maltreatment, sexual and peer victimization experiences among adolescents in residential care. (May 2019) - Indias, Sílvia; Arruabarrena, Ignacia; De Paúl, Joaquín
Abstract: Most adolescents in residential care have been through severe forms of victimization within their household. However, it is frequent to experience multiple forms of violence, and peer victimization is one of the most prevalent during adolescence. Trauma caused by interpersonal violence can have damaging effects on children and adolescents' health and psychosocial wellbeing. The present study aimed to measure lifetime prevalence and frequency rates of child physical and emotional abuse, neglect, domestic violence, and several types of sexual and peer victimization among adolescents in residential care. Additionally, victimization across contexts and effects of gender, age and immigrant status of the family (local vs. immigrant) were analyzed. Participants were 107 adolescents in Spanish residential care, aged 12–17 ( M age  = 15.16 years). Data was collected using thirteen items of the Juvenile Victimization Questionnaire self-report. Results indicate that over 75% of adolescents have suffered victimization by peers and siblings, over 65% have suffered child maltreatment, over 50% have witnessed family violence, and over 40% have suffered sexual victimization. Gender and immigrant status correlates show females and immigrant-family females reported higher prevalence of sexual victimization than their counterparts, and that immigrant-family adolescents reported higher rates of physical abuse, domestic violence, and peer assaults. Remarkably, few age effects were found. Moderate associations were found between child maltreatment, and peer and sibling and sexual victimization. Highlights: 77% adolescents in residential care victimized by peers, most from immigrant family. 24% suffered child maltreatment, domestic violence, peer AND sexual victimization. Psychological abuse by caregivers associated to emotional bullying by peers. Males and females in residential care show similar rates of sexual assault by peers. Immigrant-family females: 7 times more likely to report sexual victimization.